Library science and information technology (Anmol Publications, 1999)
Contents of material: Librarianship and the professional librarian. Modern documentation and information technology. The computer in the university (A discussion on computronics nas practicable applications). The miniature library: microfiche technology. Research methodology and new technology. Major issues in sofware and system selection. Ducumentation and computer output alternatives. Major issues in serial publications. Documentation of international comparative statistics (international organisations). Libraries and scientific literature: A training perspective. Resource sharing and objectives.